Inter-Organizational Islamic Study Groups: A Collaborative Approach to Conflict Resolution in Multicultural Communities - Yusup Rohmadi; Krisbowo Laksono; Aly Mashar; Siti Nurlaili Muhadiyatiningsih (UIN Raden Mas Said Surakarta, 2024)
This study aims to examine the role of inter-organizational Islamic study groups (Majelis Taklim), particularly Bidayatus Salikin, in conflict resolution within multicultural communities. The research explores strategies employed to foster and sustain peace amidst differing religious organizational perspectives and backgrounds, using Johan Galtung’s theoretical framework of peacemaking, peacekeeping, and peacebuilding. Data were collected through documentation of Majelis Taklim activities, in-depth interviews, and field observations. The findings reveal that Majelis Taklim serves as an inclusive forum that enables various religious organizations to openly discuss sensitive issues through a consensus-based (musyawarah) approach. Cross-organizational activities, such as joint religious discussions and the implementation of internal codes of conduct, effectively prevent conflict and promote group harmony. Additionally, the study group initiates peacekeeping efforts through economic empowerment programs, social outreach, and the formation of inter-organizational task forces aimed at long-term peacebuilding. These strategies not only strengthen inter-organizational relations but also generate positive social outcomes. This research concludes that inter-organizational Majelis Taklim plays a strategic role in managing diversity through holistic and inclusive approaches. Their efforts contribute significantly to building a more peaceful, tolerant, and prosperous society. The findings of this study are expected to serve as a model for similar initiatives in addressing conflict in multicultural contexts.